Feasibility study of wave-motion milling of carbon fiber reinforced plastic holes. (23rd November 2020) - Zhang, Deyuan; Shao, Zhenyu; Geng, Daxi; Jiang, Xinggang; Liu, Yihang; Zhou, Zehua; Li, Shaomin
Abstract: Carbon fiber reinforced plastic (CFRP) has been applied in aeronautics, aerospace, automotive and medical industries due to its superior mechanical properties. However, due to its difficult-to-cut characteristic, various damages in twist drilling and chip removal clog in core drilling could happen, inevitably reducing hole quality and hole-manufacturing efficiency. This paper proposes the wave-motion milling (WMM) method for CFRP hole-manufacturing to improve hole quality. This paper presents a motion path model based on the kinematics of the WMM method. The wave-motion cutting mode in WMM was analyzed first. Then, comparison experiments on WMM and conventional helical milling (CHM) of CFRP were carried out under dry conditions. The results showed that the hole surface quality of the CFRP significantly improved with a decrease of 18.1%–36% of Ra value in WMM compared to CHM. WMM exerted a significantly weaker thrust force than that of CHM with a reduction of 12.0%–24.9% and 3%–7.7% for different axial feed per tooth and tangential feed per tooth, respectively. Meanwhile, the hole exit damages significantly decreased in WMM. The average tear length at the hole exit in WMM was reduced by 3.5%–29.5% and 35.5%–44.7% at different axial feed per tooth and tangential feed per tooth, respectively. Moreover, WMM significantly alleviated tool wear. The experimental results suggest that WMM is an effective and promising strategy for CFRP hole-manufacturing.